Development Of Social Studies Teaching Materials For Islamic Elementary School Based On Scientific Integration - Yusnaldi, Eka; Nasution, Wahyudin Nur; Susanti, Eka (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to examine the development of Social Studies teaching materials for Islamic Elementary School (MI) based on Scientific Integration, determine the validity of the Social Studies teaching materials for MI based on Scientific Integration, assess the practicality of the Social Studies teaching materials for MI based on Scientific Integration, and evaluate the effectiveness of the Social Studies teaching materials for MI based on Scientific Integration. The research method used is Research and Development (R&D). The research procedure is based on the ADDIE research and development design. Data collection techniques include observation, interviews, and documentary studies. Data management and analysis use both quantitative and qualitative data analysis techniques. The results of the research show that the development of Social Studies teaching materials for MI based on scientific integration is carried out through the stages of analyzing the needs of the lecture, developing initial product, conducting product trials, revising the product, and producing a product that supports the implementation of lectures at PGMI FITK UIN-SU Medan. The Social Studies teaching materials for MI based on scientific integration, consisting of Syllabus (RPS), Teaching Book, and Student Worksheet (LKM), are found to be valid for use in the implementation of lectures in the PGMI FITK UIN-SU Medan program. Additionally, these teaching materials are practical and effective for use in the implementation of lectures in the PGMI FITK UIN-SU Medan program.